1998
DOI: 10.1089/dna.1998.17.735
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Human Herpesvirus 8 (HHV-8) Thymidine Kinase (TK) TATAA-Less Promoter by HHV-8 ORF50 Gene Product Is SP1 Dependent

Abstract: Human herpesvirus 8 (HHV-8) is a newly discovered virus closely associated with Kaposi's sarcoma and primary effusion lymphomas. When they occur in patients with AIDS, these B-cell lymphomas frequently harbor another human herpesvirus, Epstein-Barr virus (EBV). To determine the molecular mechanisms of the regulation of early gene expression by the immediate-early gene products of HHV-8 and to assess possible molecular interactions between HHV-8 and EBV, we studied the regulation of the HHV-8 thymidine kinase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 46 publications
2
36
0
Order By: Relevance
“…7 and 8). Ectopic expression of orf50 induces KSHV early gene transcription as well as complete lytic replication (15,25,51,55,58,62,64), whereas a dominant-negative orf50 counteracts induction of the lytic cycle (25). This establishes orf50 as necessary and sufficient to induce KSHV replication, a property that it shares with MHV68 orf50 (58).…”
Section: Discussionmentioning
confidence: 99%
“…7 and 8). Ectopic expression of orf50 induces KSHV early gene transcription as well as complete lytic replication (15,25,51,55,58,62,64), whereas a dominant-negative orf50 counteracts induction of the lytic cycle (25). This establishes orf50 as necessary and sufficient to induce KSHV replication, a property that it shares with MHV68 orf50 (58).…”
Section: Discussionmentioning
confidence: 99%
“…The ORF73 IRD is highly variable among individual KSHV isolates, with variations due to insertions, deletions, and point mutations but never frameshifts or nonsense codons (538). As a result, LANA-1 from different isolates contains variable numbers of acidic repeats, with the glutamine-rich region (region II), in particular, being a hot spot for amino acid variation (177,537).…”
Section: Kshv Subtypes and Geographic Variabilitymentioning
confidence: 99%
“…Although RTA transactivates the PAN promoter through direct binding to the type I RRE, mutations in the C/EBP sites outside the originally defined RRE also lead to a partial decrease in RTA activation of the PAN promoter (55). It has been suggested that, besides C/EBP␣ and CBF1, cellular factors such as OCT, CREB, K-RBP, and SP1 play roles in RTA transactivation on certain target promoters (21,44,53,61).…”
mentioning
confidence: 99%